Recurrent late complications following congenital diaphragmatic hernia repair with prosthetic patches: a case series - Bekdash Basil; Singh Baljit; Lakhoo Kokila (Journal of Medical Case Reports, 2009)
Abstract Introduction Many different prosthetic materials have been used for repair of large posterolateral congenital diaphragmatic hernias, which cannot be primarily repaired. Almost 50% of patch repaired diaphragmatic hernias will recur. The ideal prosthetic material for congenital diaphragmatic hernia repair has yet to be established. We report on two cases with unusual (calcification) and late complications related to the prosthetic material used for diaphragmatic hernia repair. Case presentation We report two cases of antenatally diagnosed left-sided diaphragmatic hernia that were repaired with a patch due to total absence of a diaphragm. Both Caucasian patients developed recurrent late graft complications. Case one was repaired on day 17 post-stabilisation and developed recurrence at 14½ months of age and again at 26 months of age. Case 2 underwent surgery on day 13 of life and developed recurrence at 4 months and again at 3 years of age. In the recurrent repairs, both synthetic and biomaterial patches were used. Both patients are well at long-term follow-up of 10 and 7 years, respectively. Conclusion The ideal choice of patch material for diaphragmatic hernia repair remains a therapeutic challenge.